The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18632/oncotarget.25851
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of SOCS3 enhances TRAIL-induced cell growth inhibition through the upregulation of DR4 expression in renal cell carcinoma cells

Abstract: BackgroundTumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a tumor-selective apoptosis inducer that is expressed in natural killer cells, whose cytotoxicity is activated by interferon (IFN). We investigated the effect of suppressor of cytokine signaling (SOCS) 3 on the expression of TRAIL receptors (DR4) and on TRAIL sensitivity in renal cell carcinoma (RCC) cells.MethodsVector expression, RNA interference and IL-6 receptor antibody tocilizumab were used to investigate the functional role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…However, survival prognostic analysis showed that abnormal SOCS3 expression was varied among the different tumors. For example, GBM patients with high expression of SOCS3 has a poorer OS, while KIRC patients exhibited the opposite result, and these results were consistent with previous in vivo and in vitro studies (13,42).…”
Section: Discussionsupporting
confidence: 90%
“…However, survival prognostic analysis showed that abnormal SOCS3 expression was varied among the different tumors. For example, GBM patients with high expression of SOCS3 has a poorer OS, while KIRC patients exhibited the opposite result, and these results were consistent with previous in vivo and in vitro studies (13,42).…”
Section: Discussionsupporting
confidence: 90%
“…The tumour immune microenvironment is associated with the therapeutic and prognostic response of tumours 36,37 . The current study revealed that SOCS1/2/3/4 expression was associated with immune cell infiltration in GBM.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have revealed the functions of several SOCS family genes and JAK/STAT pathway in kidney cancer ( Horiguchi et al, 2002c ; Stofas et al, 2014 ; Wake and Watson, 2015 ; Yabe et al, 2018 ; Liang et al, 2020b ); however, whether the expression levels of SOCS can affect the prognosis of patients with KIRC is not fully understood. Recently, with the development of unique prediction techniques, it is possible to fully understand the role of SOCS family members.…”
Section: Introductionmentioning
confidence: 99%